Energy transfer in covalent organic frameworks for visible-light-induced hydrogen evolution - Ding, San-Yuan; Wang, Peng-Lai; Yin, Guan-Lin; Zhang, Xuqiang; Lu, Gongxuan (International journal of hydrogen energy, 2019)
We report herein the use of covalent organic frameworks (COFs) to facilitate the energy transfer from sensitizer to the active sites for efficient photocatalysis. The results indicate that the photocatalytic efficiency can be apparently enhanced by using the layered COFs. The visible-light-induced hydrogen evolution rate (10.4 mmol g−1 h−1) for Pd0/TpPa-1 sensitized by Eosin Y was 10 times higher than that of Pd/C. The enhanced photocatalytic H2-production activity could be originated from the improvement of the photogenerated electron transfer in conjugated COFs. The important role of COFs in facilitating the transfer of photogenerated electrons was verified by the transient photocurrent response and the luminescence analysis. This research highlights the use of COFs to investigate the energy transfer process. •COFs were used to improve the energy transfer from sensitizer to active sites.•Enhanced photocatalytic efficiency can be achieved by using COFs.•The role of COFs in facilitating the energy transfer was proposed.